Studies on the Adsorption of Copper (II) by Activated Charcoal and its Application in the Treatment of Textile Industry Effluents - Tahira, Hajira; Khan, M. Nasiruddin; Sarwar, Anila (Biological Sciences - PJSIR, 2005)
The adsorption of divalent copper ions on activated charcoal was studied as a function of pH, amount of charcoal and the concentration of copper ions to optimize the operational conditions for the removal of copper ions using activated charcoal. The cross-interferences with other ions or matrix components of the textile industries effluents were also investigated. The applicability of Freundlich and Dubinin-Radushkevich equations for the said system was tested. Thermo- dynamic parameters, such as free energy change (DG), enthalpy change (DH), and entropy change (DS) during the adsorp- tion were computed. The treatment of textile industries wastes, containing higher concentrations of copper ions, has been evaluated using activated charcoal based on adsorption technique. The overall performance of the treatment system indicated that activated charcoal can be utilized as a potential decontaminate for the removal of copper ions from textile effluents before discharge into the hydrosphere.